2020
DOI: 10.21272/sec.4(4).151-159.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of FDI Inflow On The Environment: A Case Of The Baltic-Black Sea Region Countries

Abstract: The article summarizes the arguments within the scientific challenge on improving approaches to estimate the environmental impact of FDI inflow on the economy. The main objective of the research is to systematize the existing statistical approaches to analyze whether and how the macroeconomic determinants could impact the environment in terms of greenhouse gas emissions. Systematization of theoretical and methodological materials on solving the problem of choice of applying more or less stringent environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…However, in the study [99], the obtained results of the random effect model showed no statistically significant relationship between foreign direct investment and REC in the Eastern European and Central Asian countries during 1996-2018. Moreover, the regression analysis results of the panel data from the Baltic-Black Sea region countries during 1999-2018 [100] showed that the foreign direct investment inflow positively affects the ecological situation. At the same time, the strict standard environmental legislation and growth of greenhouse gas emissions in the analyzed countries are the main barriers in attracting foreign direct investments.…”
Section: Study Area Selectionmentioning
confidence: 99%
“…However, in the study [99], the obtained results of the random effect model showed no statistically significant relationship between foreign direct investment and REC in the Eastern European and Central Asian countries during 1996-2018. Moreover, the regression analysis results of the panel data from the Baltic-Black Sea region countries during 1999-2018 [100] showed that the foreign direct investment inflow positively affects the ecological situation. At the same time, the strict standard environmental legislation and growth of greenhouse gas emissions in the analyzed countries are the main barriers in attracting foreign direct investments.…”
Section: Study Area Selectionmentioning
confidence: 99%
“…The authors [22], within the framework of the scientific discussion, investigate the issues related to searching for and improving the existing approaches for assessing the impact of CO 2 on the state of the environment and the economic stability of the country, which will allow for the opening of new directions (providing carbon financing for economic entities, developing energy management, etc.) [23,24] in increasing the country's competitiveness and energy security.…”
Section: Energy Efficiency and Environmental Determinantsmentioning
confidence: 99%
“…In addition, the study applies the control variables that relate to the institutional and economic climate in the countries. The control variables are included because effective institutes are conducive to economic development [107,108], particularly within attracting investment [109][110][111]. From this point of view, the economic openness and effectiveness of government institutions are added to the model.…”
Section: Assessment Of the Greenfield Investment Effect On The Green ...mentioning
confidence: 99%